2018
DOI: 10.1111/cas.13877
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor β‐chain repertoire analysis of tumor‐infiltrating lymphocytes in pancreatic cancer

Abstract: Pancreatic cancer is lethal due to lack of perceptible symptoms and effective treatment methods. Immunotherapy may provide promising therapeutic choices for malignant tumors like pancreatic cancer. Tumor‐infiltrating lymphocytes (TIL) in tumor mesenchyme could recognize peptide antigens presented on the surface of tumor cells. The present study aimed to test the relationship between the T cell receptor (TCR) β repertoire of the tumor and peripheral blood, and also to investigate the intra‐tumor spatial heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 41 publications
(92 reference statements)
4
32
0
Order By: Relevance
“…Despite the infiltration of TILs and potential subtypes that could benefit from immunotherapy, TCR CDR3 sequencing suggested low T cell infiltration in RLPS patients compared with previous studies. Both the productive TCR β reads and the unique TCR β reads of RLPS specimens were lower than those in corresponding peripheral blood samples and other tumors . Low productive reads were associated with less T cell infiltration, which can be confirmed by IHC results.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Despite the infiltration of TILs and potential subtypes that could benefit from immunotherapy, TCR CDR3 sequencing suggested low T cell infiltration in RLPS patients compared with previous studies. Both the productive TCR β reads and the unique TCR β reads of RLPS specimens were lower than those in corresponding peripheral blood samples and other tumors . Low productive reads were associated with less T cell infiltration, which can be confirmed by IHC results.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, although the intratumoral TCR repertoires were less heterogeneous than the differences between tumor and blood, the median pairwise intratumoral TCR repertoires overlap was 0.38, and only 35 of 125 pairwise overlaps were 0.5 or higher. These results suggested a larger heterogeneity in RLPS than in other tumors . Analyses of TCR repertoires showed that ubiquitous sequences were rare across different sites of a single tumor, which also indicated a great spatial heterogeneity within RLPS.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations